Penerapan Metode Scrum pada Pembuatan Aplikasi Sistem Tanda Tangan Digital dengan QR Code Berbasis Website - Cahya Kamila; Yoga Rizky Putra; Tohpatti Crippa Praha (INTECH, 2022)
Sign systems that are still traditional are considered less effective and are starting to be replaced by digital because they can save resources and time compared to having to meet in person the traditional way. According to several studies that have been reviewed previously, the use of digital signatures using a QR Code based on a website has proven to be effective and efficient to implement. At this time the use of digital signatures has begun to be used in various places, because signatures that are done manually using a wet pen are considered less efficient because it requires a long process and is easy to manipulate, which causes the validity of the signature to decrease. . With these problems, we developed a Website-Based Digital Signature System for the Informatics and Computer Engineering Education Study Program, State University of Jakarta by applying the scrum method. Scrum is an additional responsive framework for developing software and managing product or application development. Scrum is a complex process in which many factors affect the final result. Based on our development, we conclude that it is proven that the existence of a website-based signature application using a QR Code can make the signature process more efficient and effective and can increase the level of validity of the signature because QR Codes are difficult to manipulate. that we created can be applied in many places and reduce the problem of the length of the process of requesting a signature.